IDEOLOGY IN INDONESIAN POLITICAL PARTY ANTHEMS: A STYLISTIC ANALYSIS AT THE LEXICOGRAMMATICAL LEVEL - Donal Fernado Lubis; Tri Arie Bowo (Lire Journal (Journal of Linguistics and Literature), 2023)
Political parties are a forum for Indonesian people from various ideological backgrounds as channels for the aspirations of a pluralistic society. The party's ideology is embodied in the vision and mission that the party aspires to when domination is obtained after the General Election is held. In this research, the anthem lyrics of the top three political parties, based on the 2019 legislative elections, were taken as the data and studied through a stylistic approach at the lexicogrammatical level to figure out the ideology in the realization of the vision and mission of the political parties. The method of the analysis applied descriptive qualitative through transitivity analysis in order to reveal the lexical and grammatical construction in the lyric. The typical processes used in each anthem characterized the cognitive frame of how the political parties set their vision and orientation towards the nation goals. It was found that the use of stylistic devices came in low frequency, including epizeuxis, parallelism, imagery, metaphor, symbolism, asyndeton and anaphora. The construction of clauses in the anthem lyrics has a significant impact in expressing the goals of political parties ideologically, so that the results of this study are expected to be an alternative reference that provides a paradigm for the voting community during the election period